Metapragmatic First-Order Politeness in Peninsular Spanish - Ardila, J. A. G. (HERMES - Journal of Language and Communication in Business, 2008)
Research on Spanish politeness has developed dramatically in the past decade. One of the most inﬂuential theses regarding Spanish politeness was posited by Hickey (1991), who, in comparing Spanish to English, concluded that Peninsular Spanish has a positive politeness model. Subsequently, a number of linguists have further compared politeness in Spain to politeness in Britain. In analysing countless samples of expressive politeness (i.e. requests, apologies, terms of address, etc.), these authors have come to the conclusion that positive politeness predominates in Spain. However, such critical tendencies ignore the latest trends in politeness studies: one year after the publication of Hickey´s (1991) essay, Watts et al. (1992) vindicated the need to discern ﬁrst-order politeness from second-order politeness, and put forward the relevance of metapragmatic discussions of politeness. Descriptivist assessments of Spanish politeness prevent linguists from attempting a metapragmatic methodology that help to determine where Spanish speakers stand in the politeness-impoliteness continuum. Nonetheless, current research on general politeness studies clearly envisages that this is a task that Spanish linguistics will need to fulﬁl in the long run. This paper offers a metapragmatic examination of linguistic politeness in Spain, based on the data obtained from 100 informants in Extremadura, aged 14 to 20. The information drawn from the survey indicates that, whilst the informants are fully aware of the politeness norms they have been taught by their parents and teachers, their linguistic performance seldom abides by such parameters.